Show that the following statement pattern is contingency. (p ∧ ~q) → (~ p ∧ ~ q) - Mathematics and Statistics

Advertisements
Advertisements
Sum

Show that the following statement pattern is contingency.

(p∧~q) → (~p∧~q)

Advertisements

Solution

p q ~p ~q p∧~q ~p∧~q (p∧~q)→(~p∧~q)
T T F F F F T
T F F T T F F
F T T F F F T
F F T T F T T

The truth values in the last column are not identical. Hence, it is contingency.

  Is there an error in this question or solution?
Chapter 1: Mathematical Logic - Exercise 1.6 [Page 16]

APPEARS IN

Share
Notifications



      Forgot password?
Use app×